Pulsed and Cyclic Voltammetric Studies of Phenols and Naphthols in Dimethylformamide in Presence of Sodium 4-Vinylbenzenesulfonate - László Kiss; András Kiss (Chemistry, 2025)
The influence of sodium 4-vinylbenzenesulfonate on the electrooxidation of phenols and naphthols was studied in dimethylformamide (DMF). The usually observed deactivation of phenol in non-aqueous environments was suppressed upon addition of sodium 4-vinylbenzenesulfonate, and signals of all studied compounds were highlighted due to the diminished background current. As in other cases, the latter is attributable to the solvent. The 4-vinylbenzenesulfonate salt underwent electroinitiated polymerization close to the electrode surface excluding all other compounds from it within the timescale of the measurements. The polymeric products were partially removed by dissolution; therefore, improved signal reproducibilities could be reached. The investigation was extended to pulsed voltammetric techniques widely used in analytical chemistry (differential pulse, normal pulse, square wave voltammetry). Among these techniques, differential pulse voltammetry showed the best performance. Therefore, during its use, the analytical usefulness of adding the unsaturated additive in optimal concentration was estimated in the case of some phenols and naphthols. Successful calibration for picric acid was attained in DMF.